Bibliometric analysis of the top-50 cited articles on COVID-19 and physical activity - Zhang, Fan; Zhang, Ying; Yu, Yaqi; Lu, Wei; Zhang, Huachun (Frontiers in Public Health, 2022)
Background: Since the 2019 novel coronavirus (COVID-19) pneumonia outbreak in late 2019, an endless stream of research has emerged surrounding physical activity. This study analyzes the 50 most influential articles on COVID-19 and physical activity over the past two years to describe the research landscape and hotspots from bibliometric citation analysis. Methods: The top-50 cited articles were extracted from the Web of Science Core Collection database, and bibliometric citation analysis was performed by Excel 2019 and VOSviewer software. Results: The top-50 articles were cited 160.48±106.90 (range: 70 to 587). Most of the articles were from the United States (14), followed by Italy (11) and England (9). The International Journal of Environmental Research and Public Health (n=10) is the journal with the top-50 cited articles. The collaboration between authors was mainly among three teams, including Smith L, Musumeci G, and Napoli C. The hotspot of research around COVID-19 and physical activity focused on lifestyle change (sedentary behavior, sitting time), mental health (depressive, anxiety, loneliness), the credibility of physical activity assessment tools (reliability, validity), and physical activity of different populations (gender, youth, children). Conclusions: Based on a bibliometric analysis of high-impact articles on COVID-19 and physical activity highlights physical activity as an essential lifestyle change and developments and hotspots in this field. These data will provide insights for future researchers regarding the direction of physical activity research in the COVID-19 pandemic.